2018
DOI: 10.1186/s13071-018-2654-6
|View full text |Cite
|
Sign up to set email alerts
|

Eight-year trend analysis of malaria prevalence in Kombolcha, South Wollo, north-central Ethiopia: a retrospective study

Abstract: BackgroundMalaria is one of the most serious public health problems in the world, and is a major public health problem in Ethiopia. Over the past years, the disease has been consistently reported as the first leading cause of outpatient visits, hospitalization and death in health facilities across the country. This study aimed to assess malaria prevalence trend in the Kombolcha Health Centre.MethodsA retrospective study was carried out in the Kombolcha Health Centre, north-central Ethiopia. Malaria cases repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

50
35
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 13 publications
50
35
16
Order By: Relevance
“…Concerning distribution of malaria prevalence by age groups, majority of reported cases were in the age group of subjects greater 15 years and above, followed by the age group 5-14 years, and under ve children. Such results have been reported by other studies [14,22,29], where males in this age groups are more susceptibility to malaria infections. In this rural area, males in the reproductive age groups (≥15 years old) are commonly breadwinners of their families, spending most of their time especially evenings outdoors when the peak biting activity of the infective mosquito is observed [30].…”
Section: Discussionsupporting
confidence: 90%
“…Concerning distribution of malaria prevalence by age groups, majority of reported cases were in the age group of subjects greater 15 years and above, followed by the age group 5-14 years, and under ve children. Such results have been reported by other studies [14,22,29], where males in this age groups are more susceptibility to malaria infections. In this rural area, males in the reproductive age groups (≥15 years old) are commonly breadwinners of their families, spending most of their time especially evenings outdoors when the peak biting activity of the infective mosquito is observed [30].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, Plasmodium infection was nearly equal with only slight variation among males and females which was comparable with a study conducted in Wolaita zone [19]. This finding was in contrast with the majority of the study done in Ethiopia [25,26] where males were highly affected by malaria than females. Both males and females are involved in outdoor activities especially males in the agricultural activities and most females travel to town for the market thus, they are exposed to the bite of Anopheles mosquitoes.…”
Section: Discussionsupporting
confidence: 80%
“…The minimum and maximum number of cases was recorded in 2013 and 2017, respectively. In this study, the confirmed malaria cases was higher than reported from other similar retrospective studies conducted in Bahirdar city 740 (5.0%) and Kombolcha town (2066, 7.52%), Ethiopia [3, 11]. However, the observed number of malaria cases was lower than reported [12, 13].…”
Section: Discussioncontrasting
confidence: 75%